2018
DOI: 10.1007/s40097-018-0273-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of ascorbic acid-mediated chitosan–copper oxide nanocomposite for anti-microbial, sporicidal and biofilm-inhibitory activity

Abstract: The chitosan-copper oxide (Chi-CuO) biopolymer nanocomposites were synthesized by a simple green chemistry method using ascorbic acid as a reducing and capping agent. The intense peak around 300 nm was observed in the UV-visible spectrum indicating the formation of CuO nanoparticles. The prepared Chi-CuO nanocomposites were characterized using energy-dispersive X-ray spectroscopy (EDX), scanning electron microscopy (SEM), X-ray diffraction spectroscopy (XRD), and Fourier transform-infrared spectroscopy (FT-IR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 30 publications
(34 reference statements)
2
11
0
Order By: Relevance
“…Logpriya et al [210] presented similar results to Farhoudian et al ey examined the antimicrobial activity of chi-CuO at 25, 50, and 100 μL.…”
Section: Antimicrobial Activities In Cuo-carbohydrate Filmssupporting
confidence: 52%
See 1 more Smart Citation
“…Logpriya et al [210] presented similar results to Farhoudian et al ey examined the antimicrobial activity of chi-CuO at 25, 50, and 100 μL.…”
Section: Antimicrobial Activities In Cuo-carbohydrate Filmssupporting
confidence: 52%
“…Logpriya et al [ 210 ] presented similar results to Farhoudian et al They examined the antimicrobial activity of chi-CuO at 25, 50, and 100 μ L. They showed the IZs for E. coli at 25 μ Land 50 μ L to be 6 mm, and at 100 μ L to be 8 mm. The IZs for B. subtilis , P. aeruginosa , and P. notatum at 25, 50, and 100 μ L concentrations were 6.5, 7, 8 mm; 6, 6.5, 8 mm; and 0, 10, 10 mm, respectively ( Table 5 ).…”
Section: Active Food Packagingmentioning
confidence: 61%
“…28 Recently, Logpriya et al has developed a chitosancopper oxide composite. 29 In that work, the antibacterial activity of the obtained composite was demonstrated. However, this composite was created without any substrate, which limits the possibilities for its real application.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, an important task to be solved is to obtain a chitosan‐copper containing composite on a substrate. In addition, the chitosan solution in Reference [29] was obtained using acetic acid, which can negatively affect the overall biocompatibility of the composite. The creation of a substrate with chitosan coating using solutions of carbonic acid instead of acetic acid should increase biocompatibility of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…Widyńska et al, (2018) found silver nanoparticls to have stronger antibiofilm effect than the Cu-NPs in all concentration. Logpriya et al, (2018) studied antibiofilm effect of chitosan-CuO nano particles and found to have 63% reduction at 100ug/ml against P. aeruginosa. Beltrán et al, (2019) Wang et al, (2019) studied glycol modified Cu9S8 NPs against implant related biofilm.…”
Section: Copper Nanoparticlesmentioning
confidence: 99%